(untitled) (IAHS Medical Journal, 2024)
Background: Neonatal Jaundice (NJ) is one of the most common causes of neonatal admission. Phototherapy is an important treatment modality for NJ. However, this treatment modality may itself result in changes of different biochemical parameters. The study aimed to evaluate the changes in serum electrolytes (Sodium, potassium and chloride) and calcium in neonates receiving phototherapy for NJ. Materials and methods: One hundred and two term neonates admitted to the Special Care Newborn Unit, Chattogram Medical College Hospital for the management of NJ by phototherapy were enrolled in this prospective observational study. Serum bilirubin, sodium, potassium, chloride and calcium were measured before and after 48 hours of phototherapy and compared. Results: The mean gestational age and mean age of admission of the neonates were 38.6±0.6 weeks and 6.42 ± .67 day respectively. The mean sodium, potassium and calcium level before therapy was respectively, 138.4±1.8 mmol/L, 4.1±0.3 mmol/L and 8.8±0.3 mg/dl. There was significant decrease in the level of mean sodium (136.4±1.6 mmol/L), potassium (3.8 ± 0.3 mmol/L) and calcium (8.4±0.4 mg/dL) after phototherapy. All neonates had normal level of serum calcium, sodium, potassium and chloride before phototherapy. After 48 hours of phototherapy, 46 (45.1%) of them had abnormal values with the incidence hypocalcaemia, hyponatraemia and hypokalemia respectively in 21.6%, 25.5% and 10.8% of the neonates. Conclusion: Neonates undergoing phototherapy are at risk of developing hyponatraemia, hypokalaemia and hypocalcaemia. Closed monitoring is essential to observe the changes in sodium, potassium and calcium and should be managed accordingly. IAHS Medical Journal Volume 6(2) December 2023; 83-86